A comparative analysis of competition before and after the adoption of the electronic trunk protector in taekwondo - Kim, D.-H.; Choi, H.; Kim, J. H.; Kim, E.-J. (World Congress of Performance Analysis of Sport IX, 2012)
This study was to compare the application, adaptation and efficiency in the development of techniques of Taekwondo competition before and after the adoption of the electronic trunk protector. Comparisons on attacking skills, techniques for scoring, comparisons by rounds, scoring style per attacking, attacking skills by scoring, scoring types between the winner and loser were considered. The matches before the adoption of the electronic trunk protector in the 2008 Beijing Olympics and 2012 London Olympics qualifications, and the matches after the adoption of the electronic trunk protector in the 2009 World Taekwondo Federation's World Cup and 2011 Gyeongju World Championship were used for the study. Additionally, Independent sample T-tests and chi-square comparisons were used for statistical comparisons. As summaries of results, there was significant difference between before and after the adoption of the electronic trunk protector as below; 1. The pushing kick attack (t=-2.784, p<.05) and fast turning kick attack (t=-3.040) for the attacking in the male matches were significant differences. Also, the spin kick attack (t=2.474, p<.05) in the attacking for the female players were significant differences between before and after the adoption although the fast-turning kick and pushing-kick attacks in female players have not shown any differences. 2. The ratio of turning kicks for male and female players for scoring were greater than other skills. However, the turning kick, downward kicks and pushing kick were increased comparing to before the adoption. 3. There was significant differences on attacking skills between winners and losers by male matches that the fast kicks (t=-2.884, p<.05) for winners and pushing-kicks (t=-2.871, p<.05) for losers were different on the comparison between before and after the adoption. In the female matches, there were no significant differences found. 4. There were no significant differences of skills in attacks at each round between before and after the adoption for male matches. However, there were significant differences of skills in attacks at each round in female matches (X2=27.22, P<.05). 5. There were no differences of scoring types in both male and female matches between before and after the adoption of the electronic trunk protector. 6. There no differences of frequencies of first attacks in both male and female matches between before and after the adoption Consequently, this study presented that the revised strategies of attacks and defences would be required in order to win a match after the adoption. Further research is required on the effectiveness of using the electronic trunk protector and human-referring has to be compared.